The Effect Of Financial Performance And Managerial Ownership On Company Value With Company Size As A Moderating Variable - Rofina Sani Asri Djanor; Teguh Erawati (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
This study was conducted to examine the Effect of Financial Performance and Managerial Ownership on Firm Value with Firm Size as Moderating Variable in consumption and chemical companies listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study uses purposive sampling in which the number of samples used is 14 companies. Furthermore, the data used in this study can be processed using multiple linear analysis. The results of this research are financial performance has a positive effect on firm value, managerial ownership has an effect on firm value, firm size can strengthen the influence/moderate financial performance on firm value, firm size can moderating managerial ownership of firm value.